Tourists’ Perception of Macau’s City Image: Based on the Analysis of User-Generated Content (UGC) Text Data - Jianqiang Yin; Jingzhao Feng; Ruochan Wu; Mengyan Jia (Buildings, 2023)
City image reflects urban culture and communication and influences tourists’ travel behavior. However, based on field investigations, it was found that Macau’s city space currently faces issues such as an imbalance in practical use efficiency, an overload of historical urban areas, and a mismatch between tourist numbers and spatial capacity. To further understand tourists’ travel experiences and influencing factors in Macau, this study uses user-generated content (UGC) textual data and takes the Macau Special Administrative Region in China as a case study. The ROST CM6.0 software and grounded theory analysis method are utilized to analyze the perceptual content and underlying influencing mechanisms of city image from the perspective of tourists. The research results show that: 1. Tourists’ perception of Macau’s city image mainly stays at the intuitive and superficial level, represented by individual landscapes such as the “Ruins of St. Paul’s”, “Grand Lisboa”, and “Galaxy”. 2. Tourists’ perception of Macau’s city image can be summarized into four main dimensions: architectural and landscape image, cultural and historical image, economic and commercial image, and spatial governance and public service image. 3. Negative aspects of tourists’ perception of Macau’s city image include infrastructure perception, tourism service perception, urban experience perception, and urban safety perception, with spatial scale perception being the most influential factor. Finally, this study proposes effective measures to optimize urban spatial resource allocation, improve urban infrastructure, enhance the spatial environment of the old city, strengthen the promotion of historical culture, improve urban transportation convenience, and enhance urban safety to provide references for enriching the theory of city image perception research and the development of urban tourism in Macau.